2022
DOI: 10.1007/s40120-022-00370-8
|View full text |Cite
|
Sign up to set email alerts
|

Atogepant for the Prevention of Episodic Migraine in Adults: A Systematic Review and Meta-Analysis of Efficacy and Safety

Abstract: Introduction:The inhibition of the calcitonin gene-related peptide (CGRP) pathway has attracted interest in pharmacological research on migraine. Atogepant is a potent, selective, orally available antagonist of the CGRP receptor approved as a preventive treatment of episodic migraine. This systematic review with metaanalysis aims to evaluate the efficacy and safety of atogepant for the prevention of episodic migraine in adult patients. Methods: Randomized, placebo-controlled, single or double-blinded trials we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Two previous meta-analyses (46,47) explored the efficacy and tolerability of atogepant for migraine prophylaxis compared to placebo, reporting contradictory results in relation to treatment tolerability. In agreement with Lattanzi et al ( 46), here we found that orally administrated atogepant was associated with higher odds of TEAEs compared to placebo, and the most common reported events were constipation and nausea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous meta-analyses (46,47) explored the efficacy and tolerability of atogepant for migraine prophylaxis compared to placebo, reporting contradictory results in relation to treatment tolerability. In agreement with Lattanzi et al ( 46), here we found that orally administrated atogepant was associated with higher odds of TEAEs compared to placebo, and the most common reported events were constipation and nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous meta-analyses (46,47) explored the efficacy and tolerability of atogepant for migraine prophylaxis compared to placebo, reporting contradictory results in relation to treatment tolerability. In agreement with Lattanzi et al.…”
Section: Discussionmentioning
confidence: 99%
“…40 Both atogepant and eptinezumab belong to the class of CGRP-receptor antagonist, have rapid onset of action and may prevent migraine by inhibiting CGRP receptor activation, therefore, reducing the vasodilatation and neurogenic inflammation process. 40 However, there are few differences between atogepant and eptinezumab. Atogepant partially inhibits both mechanosensitive Aδ and C-meningeal nociceptors, whereas anti-CGRP antibody including eptinezumab can only inhibit Aδ fibres.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of eptinezumab for migraine prevention was similar to the recently United States Food and Drug Administration (FDA)‐approved drug for preventive treatment of episodic migraine, atogepant. Results from recent meta‐analysis study showed that 10 and 30 mg of atogepant treatment was associated with reduction in mean migraine days from baseline to 12‐week treatment without increasing the incidence of AEs, and therefore, is considered effective and well‐tolerated for prevention of episodic migraine in adults 40 . Both atogepant and eptinezumab belong to the class of CGRP‐receptor antagonist, have rapid onset of action and may prevent migraine by inhibiting CGRP receptor activation, therefore, reducing the vasodilatation and neurogenic inflammation process 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation